2010
DOI: 10.1159/000317394
|View full text |Cite
|
Sign up to set email alerts
|

CCL5, CXCL10 and CXCL11 Chemokines in Patients with Active and Stable Relapsing-Remitting Multiple Sclerosis

Abstract: Objective: Chemokines are involved in the migration of inflammatory cells to the central nervous system in multiple sclerosis (MS). The aim of our study was to estimate the concentrations of CCL5, CXCL10 and CXCL11 in serum and cerebrospinal fluid (CSF) samples of relapsing-remitting MS (RRMS) patients during both relapse and stable disease, and to compare the results with those of controls. We also decided to evaluate the effect of methylprednisolone (MP) therapy on CCL5, CXCL10 and CXCL11 serum concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 53 publications
4
27
1
Order By: Relevance
“…CXCL10 is produced constitutively by macrophages, as well as by stimulated T cells and keratinocytes, and it promotes chemotaxis of T cells to sites of tissue inflammation. Elevated levels of CXCL10 have been observed in tuberculosis (2) and tuberculosis-associated immune reconstitution inflammatory syndrome (12,25) and in trypanosomiasis (5), as well as in multiple sclerosis and its relapses (19) and other neuroinflammatory conditions (10,20).…”
mentioning
confidence: 99%
“…CXCL10 is produced constitutively by macrophages, as well as by stimulated T cells and keratinocytes, and it promotes chemotaxis of T cells to sites of tissue inflammation. Elevated levels of CXCL10 have been observed in tuberculosis (2) and tuberculosis-associated immune reconstitution inflammatory syndrome (12,25) and in trypanosomiasis (5), as well as in multiple sclerosis and its relapses (19) and other neuroinflammatory conditions (10,20).…”
mentioning
confidence: 99%
“…23 More recently, Szczucinki et al found no difference in the levels of CXCL11 in the CSF of patients with active or stable relapsingremitting multiple sclerosis (MS) compared with controls. 26 However, in Mellergard's study a significant decline in CSF CXCL10 concentrations in MS patients after one year of natalizumab treatment was observed. 27 Our study provides the first experimental evidence on the CXCL11 concentration gradient between the CSF and plasma in patients with EV AM.…”
Section: -21mentioning
confidence: 91%
“…14 Literature data on CXCL11 expression in the CSF of patients with inflammatory and non-inflammatory CNS diseases are limited to TBE, neuroborreliosis and multiple sclerosis (MS) 17,22,23,26,27 Rupprecht et al showed significantly higher expression of CXCL10 in the CSF of patients with neuroborreliosis compared with controls as well as a correlation between CXCL11 levels and CSF-white cell counts. 23 More recently, Szczucinki et al found no difference in the levels of CXCL11 in the CSF of patients with active or stable relapsingremitting multiple sclerosis (MS) compared with controls.…”
Section: -21mentioning
confidence: 99%
“…We did not observe any statistically significant differences between VBP15 and prednisolone treatment with regard to disease severity, incidence, and histopathology. Furthermore, expression profiling of transcripts in spinal cord tissue revealed that VBP15 treatment led to significant reductions of several proinflammatory mediators including Ccl19, Ccl6, Ccl5, Ccl3, Ccl9, Cxcr4, Ccr2, Ccr5, Il-7, Il-16, Il-1a, Tgfb1, Irf1, Tnfsf13b, Tnfrsf13b, Tnfrsf4, Tnfsf12, Il-7r, Tlr2, Tlr9, Tlr8, Cd40, Icam1, and Vcam1 (Table 1), all of which have been previously shown to be associated with EAE pathogenesis (Alt et al 2002;Arima et al 2012;Baron et al 1993;Becher et al 2001;Bullard et al 2007;Desplat-Jego et al 2002;Fife et al 2000;Karpus and Kennedy 1997;Kohler et al 2008;Lee et al 2011;Li et al 2013;Matsuki et al 2006;Nohara et al 2001;Prinz et al 2006;Reboldi et al 2009;Ren et al 2011;Reynolds et al 2010;Skundric et al 2005;Szczucinski and Losy 2011;Veldhoen et al 2006;Zhou et al 2011;Zhu et al 2006). …”
Section: Vbp15 Reduces Cns Inflammation In Murine Experimental Autoimmentioning
confidence: 99%